Measuring Happiness: From Fluctuating Happiness to Authentic–Durable Happiness - Dambrun, Michael; Desprès, Gérard; Lac, Gérard (Frontiers in Psychology, 2012)
On the basis of the theoretical distinction between self-centeredness and selflessness (Dambrun & Ricard, 2011), the main goal of this research was to develop two new scales assessing distinct dimensions of happiness. By trying to maximize pleasures and to avoid displeasures, we propose that a self-centered functioning induces a fluctuating happiness in which phases of pleasure and displeasure alternate repeatedly (i.e. Fluctuating Happiness). In contrast, a selfless psychological functioning postulates the existence of a state of durable plenitude that is less dependent upon circumstances but rather is related to a person’s inner resources and abilities to deal with whatever comes his way in life (i.e. Authentic-Durable Happiness). Using various samples (n = 735), we developed a 10-item Scale measuring Subjective Fluctuating Happiness (SFHS) and a 13-item scale assessing Subjective Authentic-Durable Happiness (SA-DHS). Results indicated high internal consistencies, satisfactory test-retest validities, and adequate convergent and discriminant validities with various constructs including a biological marker of stress (salivary cortisol). Consistent with our theoretical framework, while self-enhancement values were related only to fluctuating happiness, self-transcendence values were related only to authentic-durable happiness. Support for the distinction between contentment and inner peace, two related markers of authentic happiness, also was found.